Finger Painting Learning to Stimulate Motor Development in Early Childhood (Journal of Primary Education, 2020)
The process of increasing of motor skills can be done with finger painting activities. The importance of finger painting activities on the development of fine motor and gross motor skills can help improve children's creativity and art. Finger painting in school is drawing activities by using fingertips and colour pulp directly to darwing media. The purpose of the study is to analyze the development of gross motor and fine motor skills in finger painting activities. This research uses qualitative research methods. The approach model used is a case study with 37 childrens of St. Arnoldus Yanssen and Aegela kindergartens the source of research data were, head of kindergarten. Teachers and parents. Data collection techniques are observation, interview, documentation. The criteria used in the research are underdeveloped (UD), beginning to develop (BD), very well developed (VD), and develop as expected (DE) according to Permendikbud about National Standards For Early Childhood Education. Data obtained from kindergarten Arnold Yanssen show that indicators using the right and left hand tendto lead criteria beginning to develop (BD). Data obtained from samples at the Aegela Kindergarten show the highest level of achievement is beginning to develop (BD) in skilled indicators using the right hand and left hand while for the underveloped achievement (UD) the highest in drawing indicators according to his ideas and doing detailed body movements . The results of this study are gross motor development and fine motor development of children in two kindergatens tend to lead to the criteria of beginning to develop for gross motor on the indicator using the right hand and left hand, while fine motor on the indicator self expression through drawing motion. Teachers in kindergarten need to increase knowledge about the development of children's gross motor and fine motor skills, as well as finger painting. It is intended that the teacher can see the full development of the child according to age and then give the children the right stimulus.